Molecular characterization of extended spectrum cephalosporin resistant Escherichia coli isolated from livestock and in-contact humans in Southeast Nigeria - Olorunleke, Solomon O.; Kirchner, Miranda; Duggett, Nicholas; AbuOun, Manal; Okorie-Kanu, Onyinye J.; Stevens, Kim; Card, Roderick M.; Chah, Kennedy Foinkfu; Nwanta, John A.; Brunton, Lucy A.; Anjum, Muna F. (Frontiers in Microbiology, 2022)
The rise in antimicrobial resistance (AMR) in bacteria is reducing therapeutic options for livestock and human health, with a paucity of information globally. To fill this gap a One-Health approach was taken by sampling livestock on farms (n = 52), abattoir (n = 8), and animal markets (n = 10), and in-contact humans in Southeast Nigeria. Cefotaxime-resistant (CTX-R) Escherichia coli was selectively cultured from 975 healthy livestock faecal swabs, and hand swabs from in-contact humans. Antimicrobial susceptibility testing (AST) was performed on all CTX-R E. coli. For isolates showing a MDR phenotype (n = 196), real-time (RT)-PCR was performed for confirmation of extended-spectrum β-lactamase (ESBLs) and carbapenemase genes. Whole-genome sequencing (WGS) was performed on a subset (n=157) for detailed molecular characterisation. The results showed CTX-R E. coli was present in 41.2% of samples, with AST results indicating 48.8% of isolates were phenotypically MDR. RT-PCR confirmed presence of ESBL genes, with blaCTX-M present in all but others in a subset (blaTEM (62.8%) and blaSHV (0.5%)) of isolates; none harboured transferable carbapenemase genes. Multi-locus sequence typing identified 34 Sequence Types (ST) distributed among different sampling levels; ST196 carrying blaCTX-M-55 was predominant in chickens. Large numbers of SNPs in the core genome of isolates, even within the same clade by phylogenetic analysis, indicated high genetic diversity. AMR genotyping indicated the predominant blaCTX-M variant was blaCTX-M-15 (87.9%), although blaCTX-M-55, blaCTX-M-64, and blaCTX-M-65 were present; it was notable that blaCTX-M-1, common in livestock, was absent. Other predominant AMR genes included: sul2, qnrS1, strB, blaTEM-1b, tetA-v2, and dfrA14, with prevalence varying according to host livestock species. A blaCTX-M-15 harbouring plasmid from livestock isolates in Ebonyi showed high sequence identity to one from river/sewage water in India, indicating this ESBL plasmid to be globally disseminated, being present beyond the river environment. In conclusion, CTX-R E. coli was widespread in livestock and in-contact humans from Southeast Nigeria. WGS data indicated the isolates were genetically highly diverse, probably representing true diversity of wild type E. coli; they were likely to be MDR with several harbouring blaCTX-M-15. Surprisingly, human isolates had highest numbers of AMR genes and pigs the least.